Integrated plasma metabolomic and cytokine analysis reveals a distinct immunometabolic signature in atopic dermatitis - Ma, Emily Z.; Deng, Junwen; Parthasarathy, Varsha; Lee, Kevin K.; Pritchard, Thomas; Guo, Shenghao; Zhang, Cissy; Kwatra, Madan M.; Le, Anne; Kwatra, Shawn G. (Frontiers in Immunology, 2024)
Importance: Disease models for atopic dermatitis (AD) have primarily focused on understanding underlying environmental, immunologic, and genetic etiologies. However, the role of metabolic mechanisms in AD remains understudied.Objective: To investigate the circulating blood metabolomic and cytokine profile of AD as compared to healthy control patients.This study collected plasma from 20 atopic dermatitis with moderate-to-severe itch (score of ≤5 on the itch Numeric Rating Scale and IGA score ≤3) and 24 healthy control patients. Massspectrometry based metabolite data were compared between AD and healthy controls. Unsupervised and supervised machine learning algorithms and univariate analysis analyzed metabolic concentrations. Metabolite enrichment and pathway analyses were performed on metabolites with significant fold change between AD and healthy control patients. To investigate the correlation between metabolites levels and cytokines, Spearman's rank correlation coefficients were calculated between metabolites and cytokines.Setting: Patients were recruited from the Johns Hopkins Itch Center and dermatology outpatient clinics in the Johns Hopkins Outpatient Center.The study included 20 atopic dermatitis patients and 24 healthy control patients.Fold changes of metabolites in AD vs healthy control plasma.In patients with AD, amino acids isoleucine, tyrosine, threonine, tryptophan, valine, methionine, and phenylalanine, the amino acid derivatives creatinine, indole-3-acrylic acid, acetyl-Lcarnitine, L-carnitine, 2-hydroxycinnamic acid, N-acetylaspartic acid, and the fatty amide oleamide had greater than 2-fold decrease (all P-values<0.0001) compared to healthy controls. Enriched metabolites were involved in branched-chain amino acid (valine, leucine, and isoleucine) degradation, catecholamine biosynthesis, thyroid hormone synthesis, threonine metabolism, and branched and long-chain fatty acid metabolism. Dysregulated metabolites in AD were positively correlated cytokines TARC and MCP-4 and negatively correlated with IL-1a and CCL20.Our study characterized novel dysregulated circulating plasma metabolites and metabolic pathways that may be involved in the pathogenesis of AD. These metabolic pathways serve as potential future biomarkers and therapeutic targets in the treatment of AD.